Smoking - Self-inflicted poisoning - Abd Razak, Dzulkifli (1995)
Tomorrow, May 31, 1995, is World NoTobacco Day. The objective of this event is to convince all who use tobacco to quit for at least 24 hours. Hopefully, this will lead to a more permanent commitment to stop smoking. The World NoTobacco Day is also intended to encourage governments, communities, groups, and persons worldwide to become aware of the hazards of tobacco use. The World Health Organization estimates that during the 1990s, approximately 3 million people will die each year as a direct result of smokingrelated illnesses, and about one third of these deaths will occur in developing countries like Malaysia.